Onion production in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Growing and handling dry bulb onion in the Caribbean by Frances Chandler 1994 CARDI Technical Bulletin 25 56pp price US$5. 00 ISSN 1018 1237